PERAN GURU DALAM PENANAMAN KARAKTER KEMANDIRIAN DAN TANGGUNG JAWAB DALAM PROSES PEMBELAJARAN (Studi Kasus Pada Guru Kelas di Sekolah Dasar Negeri Karang) - Farih Kurniawan, Wildan; Raras Nindya Pangesti, Cita; Maysaroh, Luluk (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2023)
Education is one of the important pillars in nation development. In the current era of globalization, education is not only required to produce intelligent and skilled individuals, but also individuals with noble character. An important character that needs to be instilled in students is the character of independence and responsibility. Independent character means having the ability to complete tasks and responsibilities well without depending on other people. Meanwhile, responsible character means having the awareness to accept the consequences of the actions taken and being willing to resolve them as best as possible. This case study was conducted to explain the teacher's role in building the character of independence and responsibility in the learning process. Teachers at SD Karang in Bogorejo District, Blora Regency are the subjects of research with results and discussion of characteristics, roles and inhibiting and supporting factors in cultivating the character of independence and responsibility at SD N Karang. Research results: Cultivating the character of independence and responsibility in elementary schools is an important and complex effort. Various driving and inhibiting factors need to be considered to achieve optimal results. It requires commitment and cooperation from all parties involved, namely school leaders, teachers, parents and students themselves, to create an environment conducive to character development. Keywords: Character education, independence, responsibility, learning process, teacher's role